Dependence of La0.57Sr0.38Co0.2Fe0.8O3-δ Cathode Degradation Rate on Electrode Thickness. (10th July 2019) - Shimura, Takaaki; Komatsu, Yosuke; Sciazko, Anna; He, An; Shikazono, Naoki
Abstract : The degradation factor of the La0.57 Sr0.38 Co0.2 Fe0.8 O3-δ (LSCF) cathode is investigated based on the relationship between its electrochemical performance and effective thickness. When the decrease in bulk diffusion coefficient D is assumed as the dominant factor of degradation, the effective thickness of LSCF electrode will decrease. On the other hand, the decrease in surface exchange coefficient k is the dominant factor, effective thickness will increase. From the 100 hrs experiments using LSCF electrodes with various thicknesses, degradation became severe as the LSCF thickness is decreased. This implies that the decrease in k can be the dominant factor in LSCF degradation.